Retrospective analysis of the prevalence of acute respiratory infections in children of the Ivano-Frankivsk region - P.Z. Buiak (Zaslavsky O.Yu., 2023)
Background. The article presents modern data about the prevalence and peculiarities of the course of acute respiratory viral infections in a childhood based on retrospective analysis of medical records. The purpose of this article was to analyze the epidemiology and features of acute respiratory viral infections in children based on the retrospective analysis of medical records, and reports of the Public Health Center. Materials and methods. Extracts from the medical charts of inpatients with acute respiratory pathology and statistical reports of the work of the ENT department of Ivano-Frankivsk Regional Children's Clinical Hospital for 2017-2022, which included 1,177 patients, were carefully studied. Results. The clinical features of acute respiratory infections in children hospitalized to the ENT department were as follows: age over 3 years (89 %), frequent admissions to the hospital (> 4 times a year) at the age of 4-5 years, nasal congestion (87.0 %), headache (72.0 %), body temperature above 37.9 °С (37 %), purulent nasal discharge (20 %), cough (15.6 %), general weakness (12.3 %). The average duration of the disease before hospitalization was 8.0 ± 0.2 days, and after hospitalization, it was 7.0 ± 0.1 days. It was found that those hospitalized had mostly ENT pathology, which initially was more likely to be viral (75.0 %); moreover, predominantly girls were affected (45 %), χ2 = 15.7, p < 0.05. At the same time, the proportion of combined forms of ENT diseases with a complicated course was 25 %, and boys were more likely to be affected (60 %), χ2 = 18.9, p < 0.05. Pansinusitis, on the other hand, occurred more often against the background of secondary chronic pathology (70.0 and 30.0 %, p < 0.05), χ2 = 32, p < 0.05. During all years of observation, the age group of 3 years and older prevailed among hospitalized children with acute respiratory infections. Most patients were admitted to the hospital in a condition of moderate severity. In all children hospitalized during the reporting period, we have found signs of respiratory syndrome such as nasal congestion and anosmia, sore throat, cough, purulent nasal discharge, as well as symptoms of intoxication: general weakness, headache, fever. Conclusions. The obtained data require further study and observation in the dynamics in order to stratify risk factors for the development of IgA-vasculitis in a childhood.